Mengoptimalkan Pengimplementasian Laporan Keuangan untuk Mencegah terjadinya Korupsi: Studi Kasus PT Asuransi Jiwasraya - Indriani, Riza; Harmen, Hilma; Manurung, Indah Safitri; Sikumbang, Riska Zunaidah; Pratiwi, Dian Maulina; Satria, Muhammad Rayhan; Hakim, Arif Rahman; Tamba, Jos Bram; Maulana, Abim Khaffi (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to optimize the implementation of financial statements to prevent corruption. Financial statements are defined as a record of information about a company's finances in one accounting period that describes the performance of a company. While corruption is something rotten, evil and destructive, based on this fact, acts of corruption involve; something immoral, rotten nature and circumstances, concerning the position of government agencies or apparatus, misuse of power in office due to gifts, transporting economic and political factors and placing families or groups into the office under the power of the office. This of course greatly violates company ethics, and can reduce the company's image. The research method used is descriptive qualitative with data collection through literature studies from various relevant journals. The results showed that financial reports have a significant relationship with corruption. Where corruption is a violation of financial ethics through the practice of embezzlement of funds, and misuse of company assets.